Full light and soil drought constrain plant growth in Mediterranean cliffs: the case of Primula palinuri Petagna. (4th July 2018) - Aronne, Giovanna; Arena, Carmen; De Micco, Veronica; Giovanetti, Manuela; Buonanno, Maurizio
Abstract: In any biogeographical region, cliffs shelter a larger number of relict species than do the surrounding areas. To develop effective conservation strategies, experimental studies are needed. We focused on Mediterranean coastal cliffs and on Primula palinuri Petagna, an endangered narrow-endemic plant, included in the IUCN Red List and chosen as a key species. The hypothesis was that light intensity and soil water availability could affect survival and growth of juvenile plants. To avoid the bias of other cliff environmental factors and to overcome problems of cliff site inaccessibility, we performed an ex-situ experiment. The effect of two light regimes and two soil water availability conditions on survival and morpho-functional traits were analysed. Plants grown under reduced light intensity and wet soil showed no reduction in survival and performed very well in terms of growth and storage accumulation. By contrast, full light and dry soil proved to be detrimental conditions. Overall results suggested that cliff environmental conditions play an important role in conservation of narrow-endemic species. The decreasing trend of the already severely fragmented populations of P. palinuri and the ongoing increasing aridity is likely to contribute to a further reduction of the already narrow distribution this cliff relict species.